BOPS: a Matlab toolbox to batch musculoskeletal data processing for OpenSim. Issue 10 (7th September 2021) - Bedo, Bruno L. S.; Mantoan, Alice; Catelli, Danilo S.; Cruaud, Willian; Reggiani, Monica; Lamontagne, Mario
Abstract: This paper presents Batch OpenSim Processing Scripts (BOPS), a Matlab toolbox for batch processing common OpenSim procedures: Inverse Kinematics, Inverse Dynamics, Muscle Analysis, Static Optimization, and Joint Reaction Analysis. BOPS is an easy-to-use and highly configurable tool that aims to reduce the time required to process large datasets, thus fostering the adoption of musculoskeletal modeling and simulations in daily practice. Its graphical user interface includes pre-defined setup files and has been designed to fulfill the needs of different research projects by simplifying the customization of the procedures, facilitating the analysis, and boosting research group collaborations. BOPS is released under Apache License 2.0, and its source code is freely available on SimTK and GitHub.